Investigating the use of SIFT for facial expression recognition - Zhong, Nan. (2013)
Scale Invariant Feature Transform (SIFT) proposed by David Lowe has been widely and successfully applied to object recognition. However, in recent decades researchers have paid more attention to face study, such as face recognition and facial expression recognition. This paper illustrates an investigation of applying SIFT to facial expression recognition. In this article, a standard smile process is set as the study object. After some basic analysis, the key-point locations which are most related to smile process have been proposed. After analyzing the SIFT key-points located along the concerned regions the movements of muscles can be illustrated.